Electrogalvanism in Oral Implantology: A Systematic Review - Meriem Amine; Wiam Merdma; Khalid El Boussiri (Hindawi Limited, 2022)
Purpose. The objective of this work is to study galvanic corrosion of different couples of prosthetic and implant alloys through the realization of a systematic review. Materials and Methods. An electronic search was performed on Pubmed, Google Scholar, Scopus, ScienceDirect, EbscoHost, and Web of Science for published studies related to electrogalvanism in oral implantology. The keywords used were "dental implants" and "galvanic corrosion." Two independent readers read the scientific articles. Results. From 65 articles initially identified, only 19 articles met the eligibility criteria. The evaluation of the selected articles allowed us to determine the parameters compared, such as the resistance to galvanic corrosion, the influence of fluorine and pH on the electrochemical behavior, and the release of metal ions and their cytotoxicity. Indeed, Ti6Al4V and precious alloys coupled to titanium were found to be the most resistant to galvanic corrosion, followed by cobalt-chromium alloys and nickel-chromium alloys which were least resistant. This resistance decreases with increasing fluorine concentration and with decreasing pH of the environment. Discussion. The implant-prosthetic system's galvanic resistance is influenced by many intrinsic factors: alloy composition and surface condition, as well as extrinsic factors such as pH variations and amount of fluorine. The effects of oral electrogalvanism are essentially the result of two main criteria: effects due to electric currents generated by corrosion and effects due to the release of metal ions by corrosion. Conclusion. To avoid this phenomenon, it is wise to follow the proposed recommendations such as the use of the minimum of distinct metals as much as possible, favoring the commercially pure titanium implant of Ti6Al4V, opting for the choice of couples, titanium/titanium, favoring daily mouthwashes of 227 ppm of fluoride, and avoiding fluorinated acid solutions.